Infant Serum and Maternal Milk Vitamin B-12 Are Positively Correlated in Kenyan Infant-Mother Dyads at 1–6 Months Postpartum, Irrespective of Infant Feeding Practice1-3. Issue 1 (25th January 2018) - Williams, Anne M; Stewart, Christine P; Shahab-Ferdows, Setareh; Hampel, Daniela; Kiprotich, Marion; Achando, Beryl; Lin, Audrie; Null, Clair A; Allen, Lindsay H; Chantry, Caroline J
Abstract: Background: Vitamin B-12 is an essential nutrient required for many functions including DNA synthesis, erythropoiesis, and brain development. If maternal milk vitamin B-12 concentrations are low, infants may face elevated risks of deficiency when exclusively breastfed. Objective: We evaluated cross-sectional associations between infant serum vitamin B-12 concentrations and maternal milk vitamin B-12 concentrations at 1–6 mo postpartum among an unsupplemented population in rural western Kenya, and assessed biological demographic, and dietary characteristics associated with adequate infant serum vitamin B-12. Methods: We modeled 1 ) infant serum vitamin B-12 using maternal milk vitamin B-12 concentration with linear regression; and 2 ) adequate (>220 pmol/L) infant serum vitamin B-12 using hypothesized biological, demographic, and dietary predictors with logistic regression. In both models, we used generalized estimating equations to account for correlated observations at the cluster-level. Results: The median (quartile 1, quartile 3) infant serum vitamin B-12 concentration was 276 pmol/L (193, 399 pmol/L) and approximately one-third of infants had serum vitamin B-12 ≤220 pmol/L, indicating that they were vitamin B-12 depleted or deficient. There was a positive correlation between maternal milk and infant serum vitamin B-12 ( r = 0.36, P < 0.001) and in multivariable analyses, maternal milk vitamin B-12 concentration was significantly associated with infant serum vitamin B-12 adequacy ( P -trend = 0.03). Conclusions: Despite a high prevalence (90%) of maternal milk vitamin B-12 concentrations below the level used to establish the Adequate Intake (<310 pmol/L), there was a low prevalence of infant vitamin B-12 deficiency. We found few factors that were associated with infant vitamin B-12 adequacy in this population, including infant feeding practices, although maternal vitamin B-12 status was not measured. The contribution of maternal milk to infant vitamin B-12 status remains important to quantify across populations, given that maternal milk vitamin B-12 concentration is modifiable with supplementation. This trial was registered at clinicaltrials.gov as NCT01704105.